Evaluation on the performance of single and dual frequency low cost GPS module observation using geodetic antenna - Atunggal, Dedi; Ma'ruf, Bilal; Sunantyo, T Aris; Rokhmana, Catur Aries (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2018)
GPS modules have been used for various applications in recent years. Its early development came in parallel with the advancement of Unmanned Aerial Vehicle (UAV) technology. Nowadays, it is also used in in geographic information system (GIS) data acquisition/census, mapping surveys, structure stability monitoring systems and many other applications. GPS modules generally have several positioning features, including standard positioning service (SPS), static positioning, precise point positioning (PPP), post processing kinematic (PPK) and real time kinematic (RTK) GPS. GPS modules in general are only equipped with a microstrip-type antenna or better known as patch antenna. Results from related research show that GPS module with this type of antenna has sub meter accuracy when used for PPK or RTK GPS method. The use of geodetic antennas is very potential to increase GPS position accuracy by up to centimeter level. This paper discusses the evaluation of GPS module measurements with geodetic type antennas for precise positioning using RTK GPS. This paper is focused on the resolution of GPS cycle ambiguity that is often expressed by the term fixing ratio and the accuracy of measurement results obtained. To provide a comprehensive description of the performance of GPS module, in this research two types of GPS module were used; single and dual frequency. Both types of GPS modules were used to conduct simultaneous observation on an open and obstructed observation location.